Understanding stakeholder views of the use of digital therapeutic interventions within children and young people’s mental health services - Gee, Brioney; Clarke, Tim; Garner, Jess; Teague, Bonnie; Coote, Georgianna; Dunne, Aoife; McGuire, Rachel; Laphan, Andrew; Rathee, Manjul; Wilson, Jon (Frontiers in Psychiatry, 2025)
BackgroundProviding the growing number of children and young people seeking mental health support with timely access to care poses a significant challenge. Increased use of digital technology in the delivery of children and young people’s mental health services has been proposed as a means of increasing access to treatment.MethodsWe conducted three interrelated studies to provide multi-perspective insights into the use of digital therapeutic interventions within children and young people’s mental health services in the UK. Study 1 used semi-structured interviews and an online survey to collect the views of digital therapeutic interventions of families who self-identified as facing additional barriers to accessing mental health support (n=13). Study 2 involved eight focus groups with children and young people’s clinicians, service managers, commissioners, and policy leads (n=28), exploring participants’ views and experiences of implementing and sustaining digital therapeutic interventions. Study 3 was a consensus exercise which aimed to identify actions needed to bridge the gap between the development and use of digital therapeutic interventions for children and young people’s mental health through focus groups with parents/carers and professionals (n=17), and three Delphi-survey rounds.ResultsOur findings revealed considerable enthusiasm for the increased use of digital mental health interventions for children and young people across stakeholder groups, but also identified key barriers to their implementation. Actions perceived to facilitate more effective implementation included: a) co-producing interventions, commissioning decisions and implementation plans with children and parents/carers, b) enhancing national guidance and local leadership, c) integration of digital offers within existing clinical pathways, and d) efforts to ensure accessibility and inclusivity.DiscussionDigital therapeutic interventions offer a promising solution to the challenge of improving access to mental health support for children and young people. Strengthened guidance and leadership, sustained funding and further evidence-generation are urgently needed to enable this promise to be realised.